A new early Holocene human skeleton from Brazil: implications for the settlement of the New World - Neves, Walter A. (2005)
Increasing skeletal evidence from the U.S.A., Mexico, Colombia, and Brazil strongly suggests that the first settlers in the Americas had a cranial morphology distinct from that displayed by most late and modern Native Americans. The Paleoamerican morphological pattern is more generalized and can be seen today among Africans, Australians, and Melanesians. Here, we present the results of a comparative morphological assessment of a late Paleoindian/early archaic specimen from Capelinha Burial II, southern Brazil. The Capelinha skull was compared with samples of four Paleoindian groups from South and Central America and worldwide modern groups from W.W. Howells’ studies. In both analyses performed (classical morphometrics and geometric morphometrics), the results show a clear association between Capelinha Burial II and the Paleoindians, as well as Australians, Melanesians, and Africans, confirming its Paleoamerican status.